Anaerobic digestion of food waste coupled with biogas upgrading in an outdoors algal-bacterial photobioreactor at pilot scale. (15th September 2022) - Marín, David; Méndez, Lara; Suero, Irene; Díaz, Israel; Blanco, Saúl; Fdz-Polanco, María; Muñoz, Raúl
Graphical abstract: Highlights: Pilot scale validation of food waste digestion coupled to photosynthetic upgrading. Biogas production of 68 ± 8 L d -1 at a loading rate of 0.86 g VS L -1 d -1 (35 °C, 1 bar) Maximum recovery efficiencies of 60 and 100% were achieved for TN and TP. CO2 removal efficiencies of 90% were achieved in biomethane. CH4 concentrations > 93% were achieved in biomethane. Abstract: This work aimed at integrating the anaerobic digestion of food waste (FW) with photosynthetic biogas upgrading at pilot scale in order to obtain a high quality biomethane and a nutrient-laden algal biomass as the main byproducts from FW treatment. The performance of a 100 L anaerobic digester treating food waste integrated via raw biogas and digestate injection with a 1.2 m 2 outdoors high-rate algal pond (HRAP) was evaluated. Biogas production in the digester averaged 790 ± 89 mL g VSin -1 (68 ± 8 L d -1 ) (35 °C, 1 bar) at a loading rate of 0.86 g VS L -1 d -1 and a steady state chemical oxygen demand removal efficiency of 83 ± 7%. The biogas produced (60% CH4 / 39% CO2 ) was upgraded in a 2.5 L absorption column interconnected with the HRAP via culture broth recirculation at a liquid to biogas ratio of 2, resulting in a maximum CO2 removal efficiency of 90% and a maximum CH4 content of 93.9%. The HRAP, supplied with the centrifuged liquid digestate supplemented with synthetic wastewater (5.0 ± 1.1 L d -1, Total nitrogen (TN) = 793 ± 110 mg N L -1, P-PO4 3- = 39 ± 19 mg P L -1 ), supported TN and total phosphorus maximum removal efficiencies of 100% in both cases. Pseudoanabaena sp. and Chlorella vulgaris were identified as the dominant species.